1997
DOI: 10.1111/j.1399-0004.1997.tb02552.x
|View full text |Cite
|
Sign up to set email alerts
|

Is the frequency of Robinow syndrome relatively high in Turkey? Four more case reports

Abstract: We describe the clinical features of Robinow syndrome in the children of four Turkish couples. All the patients had cardinal features of this condition, such as short stature, frontal bossing, hypertelorism, short upturned nose with anteverted nares, micrognathia, mesomelic shortening of the forearms, vertebral and costal anomalies and hypoplastic genitalia. In contrast to reports in the literature, one patient showed extensive webbing of the toes and epigastric hernia. Parental consanguinity was present in tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 8 publications
0
8
0
2
Order By: Relevance
“…Figures were considered above standard when higher than the 97.5th centile, and below standard when lower than the 2.5th centile (outside the normal range mean AE 1.96 SD). Fifty patients from the literature with the diagnosis of RS and a detailed clinical description were also included in the study; 24 (14 males and 10 females) with RRS and 26 (16 males and 10 females) with DRS [Robinow et al, 1969;Vera-Roman, 1973;Wadlington et al, 1973;Kelly et al, 1975;Wadia et al, 1978;Portnoy, 1979;Petit et al, 1980;Shprintzen et al, 1982;Menon et al, 1983;Bain et al, 1986;Bhandari et al, 1988;Nájera-Martinez et al, 1988;Vila-Coro et al, 1988;Glaser et al, 1989;Kumar and Puri, 1989;Schönau et al, 1990;Webber et al, 1990;Wiens et al, 1990;Schorderet et al, 1992;López et al, 1996;Aksit et al, 1997;Guuillén-Navarro et al, 1997;Al-Ata et al, 1998;Balci et al, 1998;Soliman et al, 1998;Kantaputra et al, 1999;Criado et al, 2000;Kulkarni and Reddy, 2004]. The combined (personal þ literaliterature) sample consisted therefore of 88 patients, 37 with RRS and 51 with DRS.…”
Section: Methodsmentioning
confidence: 99%
“…Figures were considered above standard when higher than the 97.5th centile, and below standard when lower than the 2.5th centile (outside the normal range mean AE 1.96 SD). Fifty patients from the literature with the diagnosis of RS and a detailed clinical description were also included in the study; 24 (14 males and 10 females) with RRS and 26 (16 males and 10 females) with DRS [Robinow et al, 1969;Vera-Roman, 1973;Wadlington et al, 1973;Kelly et al, 1975;Wadia et al, 1978;Portnoy, 1979;Petit et al, 1980;Shprintzen et al, 1982;Menon et al, 1983;Bain et al, 1986;Bhandari et al, 1988;Nájera-Martinez et al, 1988;Vila-Coro et al, 1988;Glaser et al, 1989;Kumar and Puri, 1989;Schönau et al, 1990;Webber et al, 1990;Wiens et al, 1990;Schorderet et al, 1992;López et al, 1996;Aksit et al, 1997;Guuillén-Navarro et al, 1997;Al-Ata et al, 1998;Balci et al, 1998;Soliman et al, 1998;Kantaputra et al, 1999;Criado et al, 2000;Kulkarni and Reddy, 2004]. The combined (personal þ literaliterature) sample consisted therefore of 88 patients, 37 with RRS and 51 with DRS.…”
Section: Methodsmentioning
confidence: 99%
“…The phenotypic presentation and prognosis are closely related to the mode of inheritance. Cases affected by the autosomal recessive form, which is more prevalent in populations where consanguinity is common, i.e., in Turkey, Oman, and former Czechoslovakia, are more severely affected and have an adverse outcome [3][4][5]9] . Although limb shortening is of rhizomelic type in most skeletal dysplasias with dwarfi sm, Robinow syndrome presents with mesomelia or acromelia.…”
Section: Discussionmentioning
confidence: 99%
“…Both autosomal dominant and recessive forms of inheritance have been reported, suggesting that there is allelic heterogeneity. Phenotypic presentation is related to the inheritance pattern, and patients with the recessive form, which is particularly frequent in Turkey, have signifi cant vertebral anomalies and more severe mesomelic shortening of the arms [2,4,5] . Recently, the gene for the autosomal recessive Robinow syndrome, the ROR2 gene, has been mapped on the long arm of chromosome 9 [2] .…”
Section: Introductionmentioning
confidence: 99%
“…Over 100 cases of RS have been reported to date, with an incidence of 1:500,000 with no sex preference [Tamhankar et al, ]. Autosomal recessive RS had been described in patients from various ethnic groups [Nazer et al, ; Balci et al, ; Aksit et al, ; Afzal et al, ; Kulkarni and Reddy, ; Mazzeu et al, ; Mehawej et al, ; Tamhankar et al, ]. Although, molecular studies were reported only in one Egyptian family with ARRS [Ali et al, ], other previous reports suggested AR inheritance in Egyptian patients with RS [El‐Ruby et al, ; Meguid and Aglan, ; Temtamy et al, ].…”
Section: Discussionmentioning
confidence: 99%